Análise cinemática da marcha de idosos em terreno plano, inclinado e declinado com transporte manual de carga - Silva, George Luis Coelho (2012)
The objective of this study was to analyze the kinematics of gait in the elderly, considering the manual transport of loads on the flat, inclined and declined. Fifteen healthy elderly with mean age of 63.07 (± 1.22 years) volunteered to participate in a protocol that involved 20 minutes of walking on flat ground, carrying grocery bags with 10% of body mass. The march was filmed every 05minutes of travel on the flat, inclined and declined, where the elderly went up and down a ramp with a slope of 11. The results show that a slope in the elderly and decrease the length of the last frequency and increase the length of the right step, increase the time of the last step, the double support and the single support and increase the angle of dorsiflexão of the ankle, first peak knee flexion, hip flexion, extension and trunk range of motion of ankle and hip. In ground declined the opposite occurs in the frequency and length of stride right step, but the stride length decreases. Times last step, double support and single support decreases, so does the angle of ankle plantar flexion, the second peak knee flexion and hip extension. A similar behavior was observed in hill land declined in plantar flexion and range of motion of the ankle and the first peak knee flexion. These findings prove that the slope and the slope of the terrain variables modify the spatial, temporal and angular gait of elderly people. The manual transport of loads caused changes in the spatial parameters of gait in the elderly on the flat and inclined angle on the flat, inclined and declined and reduction of temporal parameters on a slope. The march of time 5,10,15 and 20 minutes changes the parameters spatial, temporal and angular gait, showing that the elderly constantly adapt to the demands imposed by the travel time. The changes observed in this study indicate that older people should avoid walking for more than five minutes with the manual transport of loads greater than 10% of body weight on a slope and declined. These findings contribute to the development of preventive strategies designed to reduce the risk of injury during occupational activities and daily life.